Fungsi Modal Sosial Dalam Meningkatkan Kesejahteraan Ekonomi - Mega Ayu Asmara; Izzatul Ilmiyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Production is a process and the provision of goods and services in accordance with the wishes, Needs and benefits for the community. In general, production has factors namely capital, labor, land and organization. The production proces plays a role a a determinant of the level of human welfare. In this study, focuses on roof tile production in Karang Penang Sampang. Tile is an object made of soil that serves as the roof of the house to protect it from the sun and rain. Basically, sosial capital is an interaction that has norms, network and trust between individuals and other individuals or groups. Sosial capital is also related to the marketing process, because in marketing there i social interaction in various ways online (sosial media) and offline (face to face). Socio-economics is also explained by an economic thinker, namely Imam Al-Ghazali which started from a concept of Islamic welfare function. Welfare (maslahah) has a purpose for the good of the world and the hereafter.Imam Al-Ghazali main idea is a common welfare stated in the maqasid sharia. The approach used is a case study namely research that explores a phenomenon in time and individual or group activities, and collect detailed information using various data collection procedures. This case study is very relevent to the function of social capital for producing roof tiles and empowering technology as a modern tool to market roof tile in Karang Penang Sampang.